TINJAUAN TENTANG KELAYAKAN SARANA DAN PRASARANA WORKSHOP PROGRAM KEAHLIAN TATA KECANTIKAN RAMBUT SMKN 7 PADANG - Resmita, Resmita; Hayatunnufus, Hayatunnufus; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The study aims to examine more deeply about the Facility and Infrastructureworkshop Hair Beauty Treatment SMK N 7 Padang. The research method used isdescriptive quantitative, data obtained by using Guttman scale observation guidance.Data were analyzed using percentage technique and categorization of values.Population and Sample are all facilities and infrastructures in Workshop of BeautyBeauty SMK N 7 Padang In 2015/2016. The results of the study stated that thestandard feasibility of hair care facilities has a percentage score of 69% withMedium category, the means of pruning and washing hair has a percentage score of75% with Medium category, the feasibility of hair styling facilities have a percentagescore of 69% with Medium category. The size of the hair care practice room with anaverage percentage score of 80% standard fulfillment, practice room pruning andhair washing 60% categorized very low, hair styling with a percentage of 40%. Thefeasibility of building a hair treatment room, trimming room and hair wash and hairstyling room is fulfilled with a 75% percentage score of moderate category.Keywords: Facilities, Infrastructure workshop, Hair Beauty